Social and cultural pluralism in the Caribbean. Authors: Dorothy L. Keur, Vera Rubin, [a.o.] (The New York Academy of Sciences, 1960)
Papers of a conference [...] New York, May 27, 28, 1959. Annals of the New York Academy of Sciences. Vol. 83, 1960, January 20, Art. 5, p. 761-916.